f(

g(0, 1,

R

↳Dependency Pair Analysis

F(x,y,z) -> G(x,y,z)

G(0, 1,x) -> F(x,x,x)

Furthermore,

R

↳DPs

→DP Problem 1

↳Forward Instantiation Transformation

**G(0, 1, x) -> F(x, x, x)**

f(x,y,z) -> g(x,y,z)

g(0, 1,x) -> f(x,x,x)

On this DP problem, a Forward Instantiation SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

F(x,y,z) -> G(x,y,z)

F(0, 1,z') -> G(0, 1,z')

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳FwdInst

→DP Problem 2

↳Forward Instantiation Transformation

**F(0, 1, z') -> G(0, 1, z')**

f(x,y,z) -> g(x,y,z)

g(0, 1,x) -> f(x,x,x)

On this DP problem, a Forward Instantiation SCC transformation can be performed.

As a result of transforming the rule

no new Dependency Pairs are created.

G(0, 1,x) -> F(x,x,x)

The transformation is resulting in no new DP problems.

Duration:

0:00 minutes